'Lightbulb' moments in higher education: peer-to-peer support in engineering education. Issue 4 (8th August 2021) - Maccabe, Rebecca; Fonseca, Tânia Dias
ABSTRACT: Peer-to-peer programs are growing in popularity in higher education (HE) due to institutions' increased interest in engaging students as partners in learning and teaching. This study explores one institution's approach to engaging level 5 and level 6 undergraduate students as teaching assistants (TAs) in engineering to support the first-year transition and academic success. The study focuses on the effect of the pilot program on the peer mentors i.e. the TAs, rather than on the peer mentees. An online questionnaire was designed to investigate TAs' experiences of participating in a student-staff role, and the impact the role had on their academic and non-academic skills development. The findings show that the TA role contributed to enhanced subject understanding and transferable skill development, particularly communication and learning skills. The main attribute valued by TAs was helping others and making a positive impact, contributing to their sense of belonging.